Jump to navigation Jump to search

General

Display information for equation id:math.3487.1 on revision:3487

* Page found: Formula:KLS:09.05:07 (eq math.3487.1)

(force rerendering)

Cannot find the equation data in the database. Fetching from revision text.

Occurrences on the following pages:

Hash: 3f937375688061586f5dd69292924a5b

TeX (original user input):

{\displaystyle C_n=\frac{n(n+\alpha+\beta+N+1)(n+\beta)}{(2n+\alpha+\beta)(2n+\alpha+\beta+1)}}

TeX (checked):

{\displaystyle C_{n}={\frac {n(n+\alpha +\beta +N+1)(n+\beta )}{(2n+\alpha +\beta )(2n+\alpha +\beta +1)}}}

LaTeXML (experimental; uses MathML) rendering

MathML (8.571 KB / 1.269 KB) :

C n = n ( n + α + β + N + 1 ) ( n + β ) ( 2 n + α + β ) ( 2 n + α + β + 1 ) subscript 𝐶 𝑛 𝑛 𝑛 𝛼 𝛽 𝑁 1 𝑛 𝛽 2 𝑛 𝛼 𝛽 2 𝑛 𝛼 𝛽 1 {\displaystyle{\displaystyle{\displaystyle C_{n}=\frac{n(n+\alpha+\beta+N+1)(n% +\beta)}{(2n+\alpha+\beta)(2n+\alpha+\beta+1)}}}}
<math xmlns="http://www.w3.org/1998/Math/MathML" id="p1.1.m1.1" class="ltx_Math" alttext="{\displaystyle{\displaystyle{\displaystyle C_{n}=\frac{n(n+\alpha+\beta+N+1)(n%&#10;+\beta)}{(2n+\alpha+\beta)(2n+\alpha+\beta+1)}}}}" display="inline">
  <semantics id="p1.1.m1.1a">
    <mrow id="p1.1.m1.1.5" xref="p1.1.m1.1.5.cmml">
      <msub id="p1.1.m1.1.5.1" xref="p1.1.m1.1.5.1.cmml">
        <mi id="p1.1.m1.1.1" xref="p1.1.m1.1.1.cmml">C</mi>
        <mi id="p1.1.m1.1.2.1" xref="p1.1.m1.1.2.1.cmml">n</mi>
      </msub>
      <mo id="p1.1.m1.1.3" xref="p1.1.m1.1.3.cmml">=</mo>
      <mstyle displaystyle="true" id="p1.1.m1.1.4" xref="p1.1.m1.1.4.cmml">
        <mfrac id="p1.1.m1.1.4a" xref="p1.1.m1.1.4.cmml">
          <mrow id="p1.1.m1.1.4.2" xref="p1.1.m1.1.4.2.cmml">
            <mi id="p1.1.m1.1.4.2.1" xref="p1.1.m1.1.4.2.1.cmml">n</mi>
            <mo id="p1.1.m1.1.4.2.18" xref="p1.1.m1.1.4.2.18.cmml"></mo>
            <mrow id="p1.1.m1.1.4.2.19" xref="p1.1.m1.1.4.2.19.2.cmml">
              <mo stretchy="false" id="p1.1.m1.1.4.2.2" xref="p1.1.m1.1.4.2.19.2.cmml">(</mo>
              <mrow id="p1.1.m1.1.4.2.19.2" xref="p1.1.m1.1.4.2.19.2.cmml">
                <mi id="p1.1.m1.1.4.2.3" xref="p1.1.m1.1.4.2.3.cmml">n</mi>
                <mo id="p1.1.m1.1.4.2.4" xref="p1.1.m1.1.4.2.4.cmml">+</mo>
                <mi id="p1.1.m1.1.4.2.5" xref="p1.1.m1.1.4.2.5.cmml">α</mi>
                <mo id="p1.1.m1.1.4.2.4a" xref="p1.1.m1.1.4.2.4.cmml">+</mo>
                <mi id="p1.1.m1.1.4.2.7" xref="p1.1.m1.1.4.2.7.cmml">β</mi>
                <mo id="p1.1.m1.1.4.2.4b" xref="p1.1.m1.1.4.2.4.cmml">+</mo>
                <mi id="p1.1.m1.1.4.2.9" xref="p1.1.m1.1.4.2.9.cmml">N</mi>
                <mo id="p1.1.m1.1.4.2.4c" xref="p1.1.m1.1.4.2.4.cmml">+</mo>
                <mn id="p1.1.m1.1.4.2.11" xref="p1.1.m1.1.4.2.11.cmml">1</mn>
              </mrow>
              <mo stretchy="false" id="p1.1.m1.1.4.2.12" xref="p1.1.m1.1.4.2.19.2.cmml">)</mo>
            </mrow>
            <mo id="p1.1.m1.1.4.2.18a" xref="p1.1.m1.1.4.2.18.cmml"></mo>
            <mrow id="p1.1.m1.1.4.2.20" xref="p1.1.m1.1.4.2.20.2.cmml">
              <mo stretchy="false" id="p1.1.m1.1.4.2.13" xref="p1.1.m1.1.4.2.20.2.cmml">(</mo>
              <mrow id="p1.1.m1.1.4.2.20.2" xref="p1.1.m1.1.4.2.20.2.cmml">
                <mi id="p1.1.m1.1.4.2.14" xref="p1.1.m1.1.4.2.14.cmml">n</mi>
                <mo id="p1.1.m1.1.4.2.15" xref="p1.1.m1.1.4.2.15.cmml">+</mo>
                <mi id="p1.1.m1.1.4.2.16" xref="p1.1.m1.1.4.2.16.cmml">β</mi>
              </mrow>
              <mo stretchy="false" id="p1.1.m1.1.4.2.17" xref="p1.1.m1.1.4.2.20.2.cmml">)</mo>
            </mrow>
          </mrow>
          <mrow id="p1.1.m1.1.4.3" xref="p1.1.m1.1.4.3.cmml">
            <mrow id="p1.1.m1.1.4.3.20" xref="p1.1.m1.1.4.3.20.2.cmml">
              <mo stretchy="false" id="p1.1.m1.1.4.3.1" xref="p1.1.m1.1.4.3.20.2.cmml">(</mo>
              <mrow id="p1.1.m1.1.4.3.20.2" xref="p1.1.m1.1.4.3.20.2.cmml">
                <mrow id="p1.1.m1.1.4.3.20.2.1" xref="p1.1.m1.1.4.3.20.2.1.cmml">
                  <mn id="p1.1.m1.1.4.3.2" xref="p1.1.m1.1.4.3.2.cmml">2</mn>
                  <mo id="p1.1.m1.1.4.3.20.2.1.1" xref="p1.1.m1.1.4.3.20.2.1.1.cmml"></mo>
                  <mi id="p1.1.m1.1.4.3.3" xref="p1.1.m1.1.4.3.3.cmml">n</mi>
                </mrow>
                <mo id="p1.1.m1.1.4.3.4" xref="p1.1.m1.1.4.3.4.cmml">+</mo>
                <mi id="p1.1.m1.1.4.3.5" xref="p1.1.m1.1.4.3.5.cmml">α</mi>
                <mo id="p1.1.m1.1.4.3.4a" xref="p1.1.m1.1.4.3.4.cmml">+</mo>
                <mi id="p1.1.m1.1.4.3.7" xref="p1.1.m1.1.4.3.7.cmml">β</mi>
              </mrow>
              <mo stretchy="false" id="p1.1.m1.1.4.3.8" xref="p1.1.m1.1.4.3.20.2.cmml">)</mo>
            </mrow>
            <mo id="p1.1.m1.1.4.3.19" xref="p1.1.m1.1.4.3.19.cmml"></mo>
            <mrow id="p1.1.m1.1.4.3.21" xref="p1.1.m1.1.4.3.21.2.cmml">
              <mo stretchy="false" id="p1.1.m1.1.4.3.9" xref="p1.1.m1.1.4.3.21.2.cmml">(</mo>
              <mrow id="p1.1.m1.1.4.3.21.2" xref="p1.1.m1.1.4.3.21.2.cmml">
                <mrow id="p1.1.m1.1.4.3.21.2.1" xref="p1.1.m1.1.4.3.21.2.1.cmml">
                  <mn id="p1.1.m1.1.4.3.10" xref="p1.1.m1.1.4.3.10.cmml">2</mn>
                  <mo id="p1.1.m1.1.4.3.21.2.1.1" xref="p1.1.m1.1.4.3.21.2.1.1.cmml"></mo>
                  <mi id="p1.1.m1.1.4.3.11" xref="p1.1.m1.1.4.3.11.cmml">n</mi>
                </mrow>
                <mo id="p1.1.m1.1.4.3.12" xref="p1.1.m1.1.4.3.12.cmml">+</mo>
                <mi id="p1.1.m1.1.4.3.13" xref="p1.1.m1.1.4.3.13.cmml">α</mi>
                <mo id="p1.1.m1.1.4.3.12a" xref="p1.1.m1.1.4.3.12.cmml">+</mo>
                <mi id="p1.1.m1.1.4.3.15" xref="p1.1.m1.1.4.3.15.cmml">β</mi>
                <mo id="p1.1.m1.1.4.3.12b" xref="p1.1.m1.1.4.3.12.cmml">+</mo>
                <mn id="p1.1.m1.1.4.3.17" xref="p1.1.m1.1.4.3.17.cmml">1</mn>
              </mrow>
              <mo stretchy="false" id="p1.1.m1.1.4.3.18" xref="p1.1.m1.1.4.3.21.2.cmml">)</mo>
            </mrow>
          </mrow>
        </mfrac>
      </mstyle>
    </mrow>
    <annotation-xml encoding="MathML-Content" id="p1.1.m1.1b">
      <apply id="p1.1.m1.1.5.cmml" xref="p1.1.m1.1.5">
        <eq id="p1.1.m1.1.3.cmml" xref="p1.1.m1.1.3"/>
        <apply id="p1.1.m1.1.5.1.cmml" xref="p1.1.m1.1.5.1">
          <csymbol cd="ambiguous" id="p1.1.m1.1.5.1.1.cmml" xref="p1.1.m1.1.5.1">subscript</csymbol>
          <ci id="p1.1.m1.1.1.cmml" xref="p1.1.m1.1.1">𝐶</ci>
          <ci id="p1.1.m1.1.2.1.cmml" xref="p1.1.m1.1.2.1">𝑛</ci>
        </apply>
        <apply id="p1.1.m1.1.4.cmml" xref="p1.1.m1.1.4">
          <divide id="p1.1.m1.1.4.1.cmml" xref="p1.1.m1.1.4"/>
          <apply id="p1.1.m1.1.4.2.cmml" xref="p1.1.m1.1.4.2">
            <times id="p1.1.m1.1.4.2.18.cmml" xref="p1.1.m1.1.4.2.18"/>
            <ci id="p1.1.m1.1.4.2.1.cmml" xref="p1.1.m1.1.4.2.1">𝑛</ci>
            <apply id="p1.1.m1.1.4.2.19.2.cmml" xref="p1.1.m1.1.4.2.19">
              <plus id="p1.1.m1.1.4.2.4.cmml" xref="p1.1.m1.1.4.2.4"/>
              <ci id="p1.1.m1.1.4.2.3.cmml" xref="p1.1.m1.1.4.2.3">𝑛</ci>
              <ci id="p1.1.m1.1.4.2.5.cmml" xref="p1.1.m1.1.4.2.5">𝛼</ci>
              <ci id="p1.1.m1.1.4.2.7.cmml" xref="p1.1.m1.1.4.2.7">𝛽</ci>
              <ci id="p1.1.m1.1.4.2.9.cmml" xref="p1.1.m1.1.4.2.9">𝑁</ci>
              <cn type="integer" id="p1.1.m1.1.4.2.11.cmml" xref="p1.1.m1.1.4.2.11">1</cn>
            </apply>
            <apply id="p1.1.m1.1.4.2.20.2.cmml" xref="p1.1.m1.1.4.2.20">
              <plus id="p1.1.m1.1.4.2.15.cmml" xref="p1.1.m1.1.4.2.15"/>
              <ci id="p1.1.m1.1.4.2.14.cmml" xref="p1.1.m1.1.4.2.14">𝑛</ci>
              <ci id="p1.1.m1.1.4.2.16.cmml" xref="p1.1.m1.1.4.2.16">𝛽</ci>
            </apply>
          </apply>
          <apply id="p1.1.m1.1.4.3.cmml" xref="p1.1.m1.1.4.3">
            <times id="p1.1.m1.1.4.3.19.cmml" xref="p1.1.m1.1.4.3.19"/>
            <apply id="p1.1.m1.1.4.3.20.2.cmml" xref="p1.1.m1.1.4.3.20">
              <plus id="p1.1.m1.1.4.3.4.cmml" xref="p1.1.m1.1.4.3.4"/>
              <apply id="p1.1.m1.1.4.3.20.2.1.cmml" xref="p1.1.m1.1.4.3.20.2.1">
                <times id="p1.1.m1.1.4.3.20.2.1.1.cmml" xref="p1.1.m1.1.4.3.20.2.1.1"/>
                <cn type="integer" id="p1.1.m1.1.4.3.2.cmml" xref="p1.1.m1.1.4.3.2">2</cn>
                <ci id="p1.1.m1.1.4.3.3.cmml" xref="p1.1.m1.1.4.3.3">𝑛</ci>
              </apply>
              <ci id="p1.1.m1.1.4.3.5.cmml" xref="p1.1.m1.1.4.3.5">𝛼</ci>
              <ci id="p1.1.m1.1.4.3.7.cmml" xref="p1.1.m1.1.4.3.7">𝛽</ci>
            </apply>
            <apply id="p1.1.m1.1.4.3.21.2.cmml" xref="p1.1.m1.1.4.3.21">
              <plus id="p1.1.m1.1.4.3.12.cmml" xref="p1.1.m1.1.4.3.12"/>
              <apply id="p1.1.m1.1.4.3.21.2.1.cmml" xref="p1.1.m1.1.4.3.21.2.1">
                <times id="p1.1.m1.1.4.3.21.2.1.1.cmml" xref="p1.1.m1.1.4.3.21.2.1.1"/>
                <cn type="integer" id="p1.1.m1.1.4.3.10.cmml" xref="p1.1.m1.1.4.3.10">2</cn>
                <ci id="p1.1.m1.1.4.3.11.cmml" xref="p1.1.m1.1.4.3.11">𝑛</ci>
              </apply>
              <ci id="p1.1.m1.1.4.3.13.cmml" xref="p1.1.m1.1.4.3.13">𝛼</ci>
              <ci id="p1.1.m1.1.4.3.15.cmml" xref="p1.1.m1.1.4.3.15">𝛽</ci>
              <cn type="integer" id="p1.1.m1.1.4.3.17.cmml" xref="p1.1.m1.1.4.3.17">1</cn>
            </apply>
          </apply>
        </apply>
      </apply>
    </annotation-xml>
    <annotation encoding="application/x-tex" id="p1.1.m1.1c">{\displaystyle{\displaystyle{\displaystyle C_{n}=\frac{n(n+\alpha+\beta+N+1)(n%
+\beta)}{(2n+\alpha+\beta)(2n+\alpha+\beta+1)}}}}</annotation>
  </semantics>
</math>

SVG (11.607 KB / 3.382 KB) :

{\displaystyle{\displaystyle{\displaystyle C_{n}=\frac{n(n+\alpha+\beta+N+1)(n% +\beta)}{(2n+\alpha+\beta)(2n+\alpha+\beta+1)}}}}

SVG with PNG fallback (MathML can be enabled via browser plugin) rendering

MathML (2.268 KB / 446 B) :

C n = n ( n + α + β + N + 1 ) ( n + β ) ( 2 n + α + β ) ( 2 n + α + β + 1 ) {\displaystyle {\displaystyle C_{n}={\frac {n(n+\alpha +\beta +N+1)(n+\beta )}{(2n+\alpha +\beta )(2n+\alpha +\beta +1)}}}}
<math xmlns="http://www.w3.org/1998/Math/MathML" display="block" alttext="{\displaystyle {\displaystyle C_{n}={\frac {n(n+\alpha +\beta +N+1)(n+\beta )}{(2n+\alpha +\beta )(2n+\alpha +\beta +1)}}}}">
  <semantics>
    <mrow class="MJX-TeXAtom-ORD">
      <mstyle displaystyle="true" scriptlevel="0">
        <mrow class="MJX-TeXAtom-ORD">
          <mstyle displaystyle="true" scriptlevel="0">
            <msub>
              <mi>C</mi>
              <mrow class="MJX-TeXAtom-ORD">
                <mi>n</mi>
              </mrow>
            </msub>
            <mo>=</mo>
            <mrow class="MJX-TeXAtom-ORD">
              <mfrac>
                <mrow>
                  <mi>n</mi>
                  <mo stretchy="false">(</mo>
                  <mi>n</mi>
                  <mo>+</mo>
                  <mi>&#x03B1;<!-- α --></mi>
                  <mo>+</mo>
                  <mi>&#x03B2;<!-- β --></mi>
                  <mo>+</mo>
                  <mi>N</mi>
                  <mo>+</mo>
                  <mn>1</mn>
                  <mo stretchy="false">)</mo>
                  <mo stretchy="false">(</mo>
                  <mi>n</mi>
                  <mo>+</mo>
                  <mi>&#x03B2;<!-- β --></mi>
                  <mo stretchy="false">)</mo>
                </mrow>
                <mrow>
                  <mo stretchy="false">(</mo>
                  <mn>2</mn>
                  <mi>n</mi>
                  <mo>+</mo>
                  <mi>&#x03B1;<!-- α --></mi>
                  <mo>+</mo>
                  <mi>&#x03B2;<!-- β --></mi>
                  <mo stretchy="false">)</mo>
                  <mo stretchy="false">(</mo>
                  <mn>2</mn>
                  <mi>n</mi>
                  <mo>+</mo>
                  <mi>&#x03B1;<!-- α --></mi>
                  <mo>+</mo>
                  <mi>&#x03B2;<!-- β --></mi>
                  <mo>+</mo>
                  <mn>1</mn>
                  <mo stretchy="false">)</mo>
                </mrow>
              </mfrac>
            </mrow>
          </mstyle>
        </mrow>
      </mstyle>
    </mrow>
    <annotation encoding="application/x-tex">{\displaystyle {\displaystyle C_{n}={\frac {n(n+\alpha +\beta +N+1)(n+\beta )}{(2n+\alpha +\beta )(2n+\alpha +\beta +1)}}}}</annotation>
  </semantics>
</math>

SVG (7.676 KB / 2.976 KB) :

{\displaystyle {\displaystyle C_{n}={\frac {n(n+\alpha +\beta +N+1)(n+\beta )}{(2n+\alpha +\beta )(2n+\alpha +\beta +1)}}}}

PNG (0 B / 8 B) :


Translations to Computer Algebra Systems

Translation to Maple

In Maple:

Translation to Mathematica

In Mathematica:

Similar pages

Calculated based on the variables occurring on the entire Formula:KLS:09.05:07 page

Identifiers

MathML observations

0results

0results

no statistics present please run the maintenance script ExtractFeatures.php

0 results

0 results